2014
DOI: 10.1016/j.meegid.2014.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of a case of influenza A(H1N1)pdm09 and B co-infection during the epidemic season 2012–2013

Abstract: a b s t r a c tWe report the detection of one case of co-infection with influenza A(H 1 N 1 )pdm09 and B, occurred during the 2012-2013 influenza season in Sicily. The dual infection was identified in a 18-year-old boy, who was not covered by specific vaccination and who had no other pre-existing risk factors. He presented classical symptoms of influenza-like illness developing no respiratory complications. A(H 1 N 1 )pdm09 viral concentration was initially about 10-fold higher than B virus, whereas its cleara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
(10 reference statements)
0
13
1
Order By: Relevance
“…Secondly, more than 25% of all influenza-associated hospitalizations in our study occurred from May to October, thus in periods during which, both in Europe and in Italy, there is no active circulation of influenza viruses [ 23 , 24 ]. Moreover, in our database, the low number of specified and unspecified viral pneumonia codes found in the records during the influenza season could suggest a misclassification of the different viral diseases, supporting the low specificity of influenza codes observed by other authors who reported values ranging from 43% for the ICD-9 CM code 487.8 to 75% for the ICD-9 CM code 487.0 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, more than 25% of all influenza-associated hospitalizations in our study occurred from May to October, thus in periods during which, both in Europe and in Italy, there is no active circulation of influenza viruses [ 23 , 24 ]. Moreover, in our database, the low number of specified and unspecified viral pneumonia codes found in the records during the influenza season could suggest a misclassification of the different viral diseases, supporting the low specificity of influenza codes observed by other authors who reported values ranging from 43% for the ICD-9 CM code 487.8 to 75% for the ICD-9 CM code 487.0 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because coinfection with influenza A and B in adults is so unusual, coinfection should not be assumed without additional PCR testing. [3][4][5][6][7][8][9] During the 2013-2014 influenza season, an adult patient in our hospital presented with an influenza-like illness with a dual positive QuickVue Influenza A þ B Test (Quidel Corp, San Diego, Calif) result that warranted further investigation.…”
Section: Practice Of Cupping (Hijama) and The Risk Of Bloodborne Infementioning
confidence: 99%
“…Viruses of the four subtypes/lineages circulate widely in humans and 0.5%‐3.0% of influenza patients are dually infected 2,3 . Such dual infection cases are reported, but not necessarily confined to, children, young adults, pregnant women, and immunocompromised patients 2,4‐6 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Such dual infection cases are reported, but not necessarily confined to, children, young adults, pregnant women, and immunocompromised patients. 2,[4][5][6] Quantitative RT-PCR (qRT-PCR) is a sensitive and specific nucleic acid test for detecting influenza virus. 7 Viral loads determined by qRT-PCR assays are suggested to be useful markers for assessing disease severity and for predicting clinical outcomes.…”
mentioning
confidence: 99%